2013
DOI: 10.1111/neup.12070
|View full text |Cite
|
Sign up to set email alerts
|

Minor splicing pathway is not minor any more: Implications for the pathogenesis of motor neuron diseases

Abstract: To explore the molecular pathogenesis of amyotrophic lateral sclerosis (ALS), the nuclear function of TAR-DNA binding protein 43 kDa (TDP-43) must be elucidated. TDP-43 is a nuclear protein that colocalizes with Cajal body or Gem in cultured cells. Several recent studies have reported that the decreasing number of Gems accompanied the depletion of the causative genes for ALS, TDP-43 and FUS. Gems play an important role in the pathogenesis of spinal muscular atrophy. Gems are the sites of the maturation of spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
(204 reference statements)
0
9
0
Order By: Relevance
“…Given the pivotal role of these factors in splicing, upregulation of SNRNP70 (fold change = +1.8, P = 0.027; Figure a ) was validated by qRT‐PCR. There is an emerging literature to suggest that minor spliceosome elements are reduced in tissue homogenates in ALS [25]. Thus, qRT‐PCR was used to validate the downregulation of two minor spliceosome snRNP components, SNRNP48 (fold change = −17.7, P = 0.003) and SNRNP25 (fold change = −3.16, P = 0.030; Figure b ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the pivotal role of these factors in splicing, upregulation of SNRNP70 (fold change = +1.8, P = 0.027; Figure a ) was validated by qRT‐PCR. There is an emerging literature to suggest that minor spliceosome elements are reduced in tissue homogenates in ALS [25]. Thus, qRT‐PCR was used to validate the downregulation of two minor spliceosome snRNP components, SNRNP48 (fold change = −17.7, P = 0.003) and SNRNP25 (fold change = −3.16, P = 0.030; Figure b ).…”
Section: Resultsmentioning
confidence: 99%
“…[83][84][85] In the spinal cord of ALS mouse models, uridylate-rich (U) snRNAs belonging to minor spliceosome, which carries out U12-dependent splicing, are markedly reduced, as occurs in SMA. 78,86 Moreover, reduced SMN protein levels have been found in murine models of ALS. 44,87 Therefore, SMA and ALS are related motor neuron diseases that share a dysfunction of mRNA metabolism.…”
Section: Cajal Bodies In Neuropathological Disordersmentioning
confidence: 99%
“…Several lines of evidence support CB dysfunction in motor neuron diseases: i) in postnatal and mature mammalian neurons SMN and coilin co-localize in typical canonical CBs (Figs. 4C, 6D, 7A), while Gems are not detected; 26,31 ii) in cell lines and mammalian nervous tissue, the formation and integrity of CBs are dependent on ongoing transcription and snRNP biogenesis, 7,57,59,92,93 2 nuclear functions altered in motor neuron diseases; 81,86,94 iii) lack of CBs in cells derived from SMA patients correlates with decreased U4/U6-U5 tri-snRNP assembly, a maturation step of spliceosomal snRNPs that is 10-fold faster in CBs than in nucleoplasm, 62,95 and with splicing alterations of particular minor introns; 78,80 iv) coilin protein, which is lacking in Gems, scaffolds CBs and couples snRNP and snoRNP biogenesis, making CBs the center of small non-coding RNA processing; 7,33,42 and v) in motor neurons of a 3-month-old SMA patient, we have observed that lowered SMN levels induce severe depletion of canonical CBs, whereas Gems were conspicuously absent in both SMA and age-matched control neurons (Fig. 7G-I).…”
Section: 96mentioning
confidence: 99%
“…31 Depletion of another ALSassociated protein, TDP-43, can increase SMN alternative splicing and decrease its expression, 32 and may contribute to U12 minor spliceosome function. 33 Overexpression of SMN in a mutant SOD1 mouse model of ALS has been shown to alleviate motor deficits and inhibit neuron death, providing further evidence for SMN as a modifier of ALS phenotypes. 34 Interactions among ALS and SMA disease pathways are indicative of common molecular mechanisms in motor neuron loss, and may inform preclinical studies for other degenerative motor neuron diseases.…”
Section: Multifaceted Functions Of Smnmentioning
confidence: 96%